PENDIDIKAN KARAKTER DALAM PERSPEKTIF ISLAM (KAJIAN PENERAPAN PENDIDIKAN KARAKTER DI LEMBAGA PENDIDIKAN ISLAM) - Asmaun Sahlan (Fak. Tarbiyah UIN Maliki Malang, 2012)
Character building is an urgent need for Indonesia, specifically in improving the characters of current youth. Character education in the Islamic perspective equate as moral. As Holy Qur'an being the foundation of Islam in all areas of life including on the question of morality; God in His Word, which means